2021
DOI: 10.1080/15391523.2021.1911720
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical models for the facilitation of teacher professional development via video-supported collaborative learning. A review of the state of the art

Abstract: The growing use of video technologies has revealed the need for pedagogical models to support collaborative learning as part of teacher professionalization processes. We conducted a state-of-the-art review of 120 empirical studies from 2003 to 2019 to identify pedagogical models for the facilitation of teachers' professional development via video-supported collaborative learning. The study identified four pedagogical models: observation and collaborative analysis of video-recorded professional practices, colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 109 publications
0
22
0
2
Order By: Relevance
“…In recent decades, the use of video in teacher professional learning has increased (Seago, 2003). The use of video-based teaching in teacher preparation has become a significant element of teacher education programs and has shown the most significant benefits in motivation, optimized cognition, and improved classroom practices (Gaudin & Chaliès, 2015;Hamel & Viau-Guay, 2019;Hrastinski, 2021;Ramos et al, 2021;van der Linden et al, 2022). Video allows teachers to focus on students' ideas, instructional interactions, or teaching actions.…”
Section: Video As a Tool For Analyzing Student Thinking In Teacher No...mentioning
confidence: 99%
“…In recent decades, the use of video in teacher professional learning has increased (Seago, 2003). The use of video-based teaching in teacher preparation has become a significant element of teacher education programs and has shown the most significant benefits in motivation, optimized cognition, and improved classroom practices (Gaudin & Chaliès, 2015;Hamel & Viau-Guay, 2019;Hrastinski, 2021;Ramos et al, 2021;van der Linden et al, 2022). Video allows teachers to focus on students' ideas, instructional interactions, or teaching actions.…”
Section: Video As a Tool For Analyzing Student Thinking In Teacher No...mentioning
confidence: 99%
“…One material that is very suitable for applying visualization media is vibration and wave material. Learning with visual media is very useful in science learning, especially in overcoming the limitations of laboratory work and explaining materials that contain many misconceptions (Ramos et al, 2021). In addition, the results of research conducted by Gunawan et al, (2019); and Cetin, (2020) stated that visualization media helps students understand phenomena and problem solving to improve students science process skills and mastery of concepts.…”
Section: Introductionmentioning
confidence: 99%
“…In their analysis of data on user experience collected among students after the onset of the pandemic, Chen et al [15] found that the quality of the technical framework and of the content as well as the design of the user interface determine students' satisfaction with online education platforms. In 2021, Ramos et al [16] published a review on works from the pre-COVID-19 era assessing video-based learning (VBL) methods. They conclude that VBL may improve students' and teachers' educational experience when going beyond one-way video lecturing [16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Ramos et al [16] published a review on works from the pre-COVID-19 era assessing video-based learning (VBL) methods. They conclude that VBL may improve students' and teachers' educational experience when going beyond one-way video lecturing [16]. Suggested methods include collaborative VBL, collaborative video analysis, collaborative video authoring, and the use of video annotation tools [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation